Monitoring of linear alkyl benzenes (LABs) in riverine and estuarine sediments in Malaysia - Masood, Najat; Alkhadher, Sadeq A. A.; Magam, Sami M.; Halimoon, Normala; Alsukaibi, Abdulmohsen; Zakaria, Mohamad Pauzi; Vaezzadeh, Vahab; Keshavarzifard, Mehrzad; Maisara, Sawsan; Break, Mohammed Khaled (Springer, 2021)
The aim of this a pioneering research is to investigate linear alkylbenzenes (LABs) as biomarkers of sewage pollution in sediments collected from four rivers and estuaries of the south and east of Peninsular Malaysia. The sediment samples went through soxhlet extraction, two-step column chromatography purification, fractionation and gas chromatography–mass spectrometry (GC–MS) analysis. Principal component analysis (PCA) with multivariate linear regression (MLR) was used as well for source apportionment of LABs. The results of this study showed that total LAB concentration was 36–1196 ng g−1dw. The internal to external isomer ratios (I/E ratio) of LABs were from 0.56 to 3.12 indicated release of raw sewage and primary and secondary effluents into the environment of south and east of Peninsular Malaysia. Our research supported that continuous monitoring of sewage pollution to limit the environmental pollution in riverine and estuarine ecosystem.